2018
DOI: 10.5173/ceju.2018.1653
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde intrarenal surgery using the single – use flexible ureteroscope Uscope 3022 (PUSEN TM): evaluation of clinical results

Abstract: IntroductionReusable endoscopes have some limitations regarding their continued use. To sort out these problems, several disposable devices have appeared on the market. Our objective is to show our clinical results with a new digital flexible single-use ureteroscope.Materials and methodsThis study presents a prospective series of patients who underwent endoscopic surgery as treatment for renal stones using the digital disposable endoscope Uscope 3022™. Demographic, procedure and stone information were register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For intrarenal surgeries, the capacity of a flexible ureteroscope to deflect is essential since it is required for access and navigation of the renal pelvis, calyces, and diverticula [ 14 ]. Moreover, it is of the utmost importance while attempting treatment of lower pole calculi, as the lower pole of the kidney is more difficult to approach.…”
Section: Resultsmentioning
confidence: 99%
“…For intrarenal surgeries, the capacity of a flexible ureteroscope to deflect is essential since it is required for access and navigation of the renal pelvis, calyces, and diverticula [ 14 ]. Moreover, it is of the utmost importance while attempting treatment of lower pole calculi, as the lower pole of the kidney is more difficult to approach.…”
Section: Resultsmentioning
confidence: 99%
“…There is no consensus in the operative time between single-use FURS and reusable FURS. Although several studies have found that the single-use FURS have the advantage of shorter surgical time (22)(23)(24), a series of prospective comparative research between single-use FURS and reusable FURS have found no significant difference in mean operative time between these two surgical devices (7,17,18,25). As such, a prospective study with larger sample size is needed to confirm the performance of single-use and reusable FURS in terms of operative time.…”
Section: Discussionmentioning
confidence: 99%
“…The manipulation and lithotripsy effect of exible ureteroscopy are generally closely related to the clarity of ureteroscopy imaging, the bendability of head end, the left-right direction adjustability, the size, hardness and location of stones. With the popularization of electronic exible ureteroscope and the application of disposable electronic exible ureteroscope [14][15][16], the clarity of surgical imaging is greatly improved and the learning curve is further shortened, which increases the operation e ciency is better.…”
Section: Discussionmentioning
confidence: 99%